2009
DOI: 10.1002/car.1076
|View full text |Cite
|
Sign up to set email alerts
|

Information sharing and reporting systems in the UK and Ireland: Professional barriers to reporting child maltreatment concerns

Abstract: Across the UK recent policy developments have focused on improved information sharing and inter-agency cooperation. Professional non-reporting of child maltreatment concerns has been consistently highlighted as a problem in a range of countries and the research literature indicates that this can happen for a variety of reasons. Characteristics such as the type of abuse and the threshold of evidence available are key factors, as are concerns that reporting will damage the professional-client relationship. Profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 32 publications
1
41
0
1
Order By: Relevance
“…The reasons for this have been extensively discussed (Bunting, Lazenbatt, & Wallace, 2010;Hawkins & McCallum, 2001;Polnay, 2000;Raman, Holdgate & Torrens, 2012). Services organised as separate professional bureaucracies inevitably create institutional and cultural barriers, which in child protection may be exacerbated by 4 institutional anxiety about risk.…”
Section: Trends In Interprofessional Practice and Educationmentioning
confidence: 99%
“…The reasons for this have been extensively discussed (Bunting, Lazenbatt, & Wallace, 2010;Hawkins & McCallum, 2001;Polnay, 2000;Raman, Holdgate & Torrens, 2012). Services organised as separate professional bureaucracies inevitably create institutional and cultural barriers, which in child protection may be exacerbated by 4 institutional anxiety about risk.…”
Section: Trends In Interprofessional Practice and Educationmentioning
confidence: 99%
“…As an extension or subtype of attitude one may also include the dimensions of commitment, confidence, and concern. The literature on demographic variables suggests possible relationships between ethnicity and gender on reporting practices As such, ethnicity and gender were included as covariates [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Secondary sources suggest reasons as to why speech-language pathologists may fail to report alleged maltreatment. Due to the recurring theme noted in the literature highlighting a lack of pedagogical training across disciplines regarding child maltreatment and reporting methodology, further research appears indicated [25,[31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The article presents a review of 'Consent obtained prior to the infant's birth "must be both reaffi rmed and its validity established"' 'More skills to work with children and families and greater knowledge about how to work with child protective services' international literature which contributes to knowledge and understanding of mandatory reporting. In a helpful summary of the existing research evidence across a number of countries, Bunting et al (2010) highlight a number of reasons why practitioners from a range of different professional groups fail to report suspected child maltreatment including 'the threshold of evidence available ' (p. 198) and the fact that the type of abuse affects reporting decisions-with physical abuse most often reported and emotional abuse least likely to be reported. The authors also draw attention to the body of literature around professional discipline, attitudes and beliefs which have all been considered in relation to non-reporting of child maltreatment, including the often cited concern that information sharing and reporting of child abuse and neglect could impact negatively on positive professional relationships with families.…”
mentioning
confidence: 99%